SUATU TINJAUAN KEDUDUKAN LEMBAGA PERMASYARAKATAN SEBAGAI SUB SISTEM PERADILAN PIDANA DI INDONESIA - Siregar, Syawal Amry (JURNAL RETENTUM, 2019)
ndonesia which is tasked with carrying out guidance on Prisoner.The criminal justice system is a law enforcement system as a crime prevention effort. The Criminal Justice System consists of 4 components (sub-systems), namely the sub-system of the police, the sub-system of the prosecutor's office, the sub-system of the court, and the sub-system of prisons.Limitations of facilities can be an obstacle to the formation of prisoners as expected. Therefore, it is difficult to produce effective, efficient and effective coaching. This is reasonable, considering the purpose of the correctional system is ideal, while the means are very limited. As a result, each officer will experience saturation and fantasies about the ideals of correctionalism. The problem of fostering inmates cannot be separated from the discussion of criminal matters, conviction. In criminal matters that are not less important are related to the problem of why humans commit illegal acts in which the cause of crime and what is the need for sanctions for criminal law is applied.